2020
DOI: 10.21203/rs.3.rs-35019/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implications of COVID-19 in high burden HIV/TB countries: A systematic review of evidence

Abstract: Background The triple burden of COVID-19, tuberculosis and human immunodeficiency virus is one of the major global health challenges of the 21st century and in the future. In high burden HIV/TB countries, the spread of COVID-19 among people living with HIV is a well-founded concern. A thorough understanding of HIV/TB and COVID-19 pandemics is important as the three diseases interact. This may clarify HIV/TB/COVID-19 as a newly related field and play an important role in the present and future management of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The triple burden of COVID-19, human immunodeficiency virus (HIV) and hepatitis C virus (HCV) is one of the major and persistent global health challenges of the twenty-first century. The HIV, HCV and newly emerging infectious diseases such as coronavirus epidemics are expected to overlap in high HIV and HCB or HCV burden countries [ 64 ]. How COVID-19 will manifest itself in persons co-infected with HIV/HCV is still unclear [ 64 ].…”
Section: Microbial Co-infections In Hospitalized Patients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The triple burden of COVID-19, human immunodeficiency virus (HIV) and hepatitis C virus (HCV) is one of the major and persistent global health challenges of the twenty-first century. The HIV, HCV and newly emerging infectious diseases such as coronavirus epidemics are expected to overlap in high HIV and HCB or HCV burden countries [ 64 ]. How COVID-19 will manifest itself in persons co-infected with HIV/HCV is still unclear [ 64 ].…”
Section: Microbial Co-infections In Hospitalized Patients With Covid-19mentioning
confidence: 99%
“…The HIV, HCV and newly emerging infectious diseases such as coronavirus epidemics are expected to overlap in high HIV and HCB or HCV burden countries [ 64 ]. How COVID-19 will manifest itself in persons co-infected with HIV/HCV is still unclear [ 64 ]. Populations infected with HIV and HCV may be at elevated risk for severe responses if they are infected with COVID-19.…”
Section: Microbial Co-infections In Hospitalized Patients With Covid-19mentioning
confidence: 99%
“…Due to the systemic inflammation induced by chronic HIV infection and active TB, questions have been raised whether these two diseases in particular could distort the immune response to SARS-CoV-2, leading to increased mortality. Indeed, emerging evidence shows that TB and HIV are independently associated with an increased risk for COVID-19 mortality (Boulle et al, 2020; Geretti et al, 2020; Tamuzi et al, 2020). Thus, we defined the impact of HIV, TB and HIV/aTB co-infection on the magnitude, phenotypic and functional profile of the SARS-CoV-2 CD4 T cell response.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, profound lymphopenia and hyper-inflammation associated with COVID-19 could favor Mtb reactivation. These concerns are further underlined by several large epidemiological studies showing that, both HIV-1 and active TB independently associate with an increased risk of COVID-19-related death (Bhaskaran et al, 2021; Boulle et al, 2020; Brown et al, 2021; Chen et al, 2020a; Davies, 2020; Geretti et al, 2020; Tamuzi et al, 2020). It is thus an urgent research priority to investigate the profile of the SARS-CoV-2-specific T cells in patients co-infected with HIV-1 and/or active TB and to assess the impact of acute SARS-CoV-2 infection on the Mtb-specific memory CD4 T cell response.…”
Section: Introductionmentioning
confidence: 99%
“…Although a meta‐analysis of Chinese studies did not find an association between tuberculosis and COVID‐19 severity, 6 it is important to note that these results may have been affected by the clinical heterogeneity of tuberculosis cases and sample size limitations. Moreover, another systematic review recently reported an association between tuberculosis and COVID‐19, independent of HIV status, suggesting that tuberculosis patients may be more susceptible to severe COVID‐19 and death 17 . Therefore, more studies with well‐characterized tuberculosis phenotypes and COVID‐19 coinfection are needed 18 …”
Section: Discussionmentioning
confidence: 99%